SAT0544 Comparing New and Classical Diagnostic Criteria in Behçet Disease (BD). (9th June 2015) - Rodríguez Carballeira, M.; Larrañaga, J.; Solanich, X.; Solans, R.; Garcia Carus, E.; Rios, R.; Castillo, M.; Nieto, J.; Hurtado, R.; Fanlo, P.; Garcia, I.; Herranz, M.; et al.
Abstract : Background: The absence of pathognomonic serological markers of BD represents a serious difficulty for the diagnosis of Behçet's disease (BD). The International Study Group (ISBD) criteria have been repeatedly questioned by filing a suboptimal sensitivity according to some experts. Recently, a new set of International Criteria for BD (ICBD) 1 have been proposed considering oral ulcers, genital ulcers, vascular, cutaneous, or central nervous system involvement and patergy test. Each manifestation corresponds to some points and patients with ≥4 points are considered to have BD. This new criteria have shown a substantial improvement in the diagnostic sensitivity. Objectives: To compare the diagnostic sensitivity of the criteria for the classification of BD from the ISBD and the new ICBD criteria in the cohort of patients of the Spanish Registry (REGEB in the Spanish nomenclature). Methods: The demographic and clinical features of BD patients included in the REGEB were analyzed using a computerized database. This project was performed under the auspices of the Working Area of BD, on behalf of Systemic Autoimmune Diseases Group (GEAS) of the Spanish Society of Internal Medicine (SEMI). This registry started in 2009, with a multicenter, consecutive, retrospective design. Results: Up to December 2014, 573 patients from 20 Spanish hospitals were included in the REGEB. Overall, 308 (54%) patients were women and the mean (SD) age at the first manifestation of the disease was 29 (12) years (range10-73). The median delay of diagnosis was 24 months (range 0-420) and median follow-up time was 126 months (range 0-758). The majority of patients (94%) was of Caucasian origin followed by Arabic origin (4%), and African (1%). The prevalence of manifestations common in both set of criteria were: oral ulcers (94%), genital ulcers (61%), vascular (18.2%), ocular (45.2%), cutaneous (59.9%) and neurologic (12.4%) involvement. Considering ISBD criteria, 541 (94%) patients met the major criteria. Regarding minor criteria, 350 (61%) met at least two of the minor criteria. Therefore, 61% fulfilled diagnostic criteria of definite BD and the remaining of probable BD (only one minor criterion or no major criterion -in 32 cases- but with another element of high suspicion). Considering ICBD 2014 criteria, 85% of patients have 4 or more points and therefore fulfilled the diagnostic criteria of BD. 13% have 3 points (diagnostic of possible BD). Overall, 27, 9% from patients who did not fulfill definite diagnosis of BD according ISBD criteria, have at least 4 points according ICBD 2014 criteria. Conclusions: The new ICBD 2014 criteria showed higher sensitivity than ISBD for the diagnosis of BD in the REGEB cohort. References: JEADV 2014, 28, 338–347 Disclosure of Interest: None declared